Adult tetanus in Accra, why the high mortality? An audit of clinical management of tetanus - Hesse, I.F.A.; Mensah, A.; Asante, D.K.; Lartey, M.; Neequaye, A. (West African Journal of Medicine, 2005)
Background: Tetanus is a life threatening infection relatively uncommon in the developed countries but occurs frequently in developing countries with case fatality rates of 40-60%. Recent review of adult tetanus at the Korle-bu Teaching Hospital showed a high case fatality of 50%. In order to determine the factors underlying this high case fatality we conducted a retrospective clinical audit of the clinical management of adult tetanus admitted in 1994 to 2001 to the Korle-bu Teaching Hospital. Methods: Data extracted from the admission and discharge books of the Fevers' Unit of Korle-bu Teaching Hospital, Accra and patient case notes were examined and analysed. Results: Case fatality rate (CFR) varied from 25% in 1999 to 72.7% in 2001. There was no gender difference in the case fatality. There was no significant difference in the mean age of those who died and those who survived, however, the CFR rose with age. The presence of neck and a dirty wound were associated with increased CFR. The CFR correlated with the severity of tetanus and increased when an expected treatment action, wound debridement, administration of antibiotics and/or immunoglobulin, was not performed. The administration of anti-tetanus toxin was associated with an increased CFR. Conclusion: The high case fatality rate in Accra was due to inappropriate management with most of the patients not treated with immunoglobulin and antibiotics and had inadequate wound care.
Keywords: Adult tetanus; Clinical audit; Mortality